Experience of Definitive Chemoradiation for Oesophageal Cancer Within a Large Regional Cancer Treatment Centre: Improving Outcomes and Tolerability. Issue 10 (October 2018) - Lavin, V.J.; Mehta, S.; Sumra, P.; Wang, X.; Bhatt, L.; Jackson, A.S.; Sheikh, H.Y.
Abstract: Aims: To review delivery of definitive chemoradiation (dCRT) for patients with oesophageal cancer within a large regional cancer centre. To assess toxicity, tolerability and outcomes and compare with published data. Materials and methods: A retrospective review of patients undergoing dCRT between November 2009 and November 2014 was carried out. Data were collected regarding treatment completion, radiotherapy plans, toxicity, failure and death. Kaplan–Meier survival curves with a Log-rank test for significance were used for survival analysis. Results: In total, 179 patients were analysed. The median age at diagnosis was 70 years. Forty-four (24.6%) patients had T1 or T2 tumours, 113 (63.1%) T3 and 18 (10.1%) T4; 117 (65.4%) patients were node positive on initial staging. One hundred and forty patients were treated before 2012 with CRT and two adjuvant cycles of cisplatin and capecitabine. Of these, only 50% completed both adjuvant cycles of chemotherapy. Thirty-nine patients were treated after 2012 with neoadjuvant cisplatin and capecitabine followed by CRT. Of these, 92% completed all planned chemotherapy. Ninety-five per cent of patients completed radiotherapy without interruption, but only 46% completed concurrent capecitabine. The mean planning target volume (PTV) length was 13 cm (range 6.9–22.2 cm) and 27 (15%) patients had a PTV length greater than 16 cm. After a median follow-up of 19.6 months (range 3.0–71.9), 83 patients (46%) had relapsed, with 43 (24%) patients having isolated locoregional recurrence. The median overall survival was 26 months (95% confidence interval 20.2–31.8) with a 5 year overall survival rate of 19.7% (95% confidence interval 10.4–31.2). Conclusions: Our series shows comparable survival rates with published data despite an unselected population. The transition to neoadjuvant chemotherapy before CRT has improved tolerability and increased rates of completion of treatment. The locoregional failure rate remains significant and strategies for improving this, such as changing the chemotherapy back bone and radiation dose escalation, are eagerly awaited within the SCOPE-2 study. Highlights: In patients undergoing dCRT for oesophageal cancer we demonstrate a median overall survival of 26 months (95% confidence interval 20.2–31.8). A change in sequencing of chemotherapy to two neoadjuvant cycles followed by CRT appears more tolerable with completion of all planned chemotherapy of 50% and 92%, respectively. 27 (15%) patients had PTVs longer than 16 cm (the upper limit within the SCOPE-1 trial) and 25 (14%) patients had V20 greater than 25%. Despite this, pneumonitis rates were low. This indicates there is room to treat longer primaries and more involved nodal stations. After a median follow-up of 19.6 months, 83 (46%) patients had relapsed; 24% had locoregional recurrence and 12% had distant metastatic disease.